Organisational challenges, volumes of oncological activity and patients' perception during the severe acute respiratory syndrome coronavirus 2 epidemic. (August 2020) - Zuliani, Serena; Zampiva, Ilaria; Tregnago, Daniela; Casali, Miriam; Cavaliere, Alessandro; Fumagalli, Arianna; Merler, Sara; Riva, Silvia Teresa; Rossi, Alice; Zacchi, Francesca; Zaninotto, Elisa; Auriemma, Alessandra; et al.
Abstract: Background: On February 23rd, the 1st case of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was diagnosed at the University Hospital Trust of Verona, Italy. On March 13th, the Oncology Section was converted into a 22-inpatient bed coronavirus disease (COVID) Unit, and we reshaped our organisation to face the SARS-CoV-2 epidemic, while maintaining oncological activities. Methods: We tracked down (i) volumes of oncological activities (January 1st - March 31st, 2020 versus the same period of 2019), (ii) patients' and caregivers' perception and (iii) SARS-CoV-2 infection rate in oncology health professionals and SARS-CoV-2 infection–related hospital admissions of "active"' oncological patients. Results: As compared with the same trimester in 2019, the overall reduction in total numbers of inpatient admissions, chemotherapy administrations and specialist visits in January–March 2020 was 8%, 6% and 3%, respectively; based on the weekly average of daily accesses, reduction in some of the oncological activities became statistically significant from week 11. The overall acceptance of adopted measures, as measured by targeted questionnaires administered to a sample of 241 outpatients, was high (>70%). Overall, 8 of 85 oncology health professionals tested positive for SARS-CoV-2 infection (all but one employed in the COVID Unit, no hospital admissions and no treatment required); among 471 patients admitted for SARS-CoV-2 infection, 7 had an "active"' oncological disease (2 died of infection-related complications). Conclusions: A slight, but statistically significant reduction in oncology activity was registered during the SARS-CoV-2 epidemic peak in Verona, Italy. Organisational and protective measures adopted appear to have contributed to keep infections in both oncological patients and health professionals to a minimum. Highlights: Timely adoption of protective measures can protect healthcare workers and patients. Careful organisation allowed to minimally reduce oncological activity volumes. Information and psychological support are crucial to accept measures-related change. Long-term impact of containment measures on cancer care should be further explored.